Kolesterol non-HDL yang tinggi berhubungan dengan derajat stenosis arteri koroner berat pada pasien sindroma koroner kronis di RSUP Sanglah - I Made Gunarsa; Wayan Aryadana; I Made Junior Rina Artha (Intisari Sains Medis, 2022)
Introduction: Non-HDL cholesterol is a lipid parameter that describes the overall component of atherogenic lipids and is strongly correlated with apoB and sdLDL (small-dense LDL). There has been no study linking non HDL cholesterol (high density lipoprotein) with the degree of coronary stenosis based on the assessment of the previous syntax score. This study aims to prove the relationship between high non-HDL cholesterol and the degree of severe coronary artery lesions in patients with chronic coronary syndrome who underwent coronary angiography at Sanglah Hospital Denpasar.Methods: This analytical observational study was conducted at Sanglah General Hospital from June to November 2020. Sampling was carried out by consecutive sampling. Non HDL cholesterol was calculated by subtracting total cholesterol with HDL and divided into 2 categories based on ROC analysis. The syntax score was calculated based on the results of coronary angiography and was divided into 2 categories (cut off 22). The relationship between non-HDL cholesterol and the degree of coronary stenosis was assessed by chi-square test analysis.Results: Seventy-two subjects were included in this study with a mean age of 59.43±8.9 years. At the cut-off point of 104.5 mg/dL based on the ROC curve, non-HDL cholesterol had an AUC of 0.846, a sensitivity level of 80% and a specificity of 78.1% (p < 0.001). The results of bivariate analysis showed that high non-HDL cholesterol was associated with the degree of severe coronary stenosis with a prevalence ratio of 3.385 (p<0.001). Multivariate logistic regression analysis showed that high non-HDL cholesterol proved to be an independent predictor of severe coronary artery stenosis in patients with chronic coronary syndrome at Sanglah Hospital.Conclusion: High non-HDL cholesterol was shown to be independently associated with severe coronary artery stenosis in SKK subjects at Sanglah Hospital.  Pendahuluan: Kolesterol non HDL merupakan parameter lipid yang menggambarkan keseluruhan komponen lipid atherogenik dan berkorelasi kuat dengan apoB dan sdLDL (small-dense LDL). Belum ada penelitian yang menghubungkan kolesterol non HDL (high density lipoprotein) dengan derajat stenosis koroner berdasarkan penilaian skor syntax sebelumnya. Penelitian ini bertujuan untuk membuktikan hubungan kolesterol non HDL  yang tinggi dengan derajat lesi arteri koroner yang berat pada penderita sindroma koroner kronis yang dilakukan tindakan angiografi koroner di RSUP Sanglah Denpasar.Metode: : Penelitian observasional analitik ini dilakukan di Rumah Sakit Umum Sanglah dari Juni hingga November  2020. Pengambilan sampel dilakukan secara concecutive sampling. Kolesterol non HDL dihitung dengan cara mengurangi total kolesterol dengan HDL dan dibagi menjadi 2 kategori berdasarkan analisis ROC. Skor syntax dihitung berdasarkan hasil angiografi koroner dan dibagi menjadi 2 kategori (cut off 22). Hubungan antara kolesterol non HDL dan derajat stenosis koroner dinilai dengan analisis chi-square test.Hasil: Tujuh puluh dua subyek dilibatkan dalam penelitian ini dengan dengan rerata usia 59,43±8,9 tahun. Pada nilai titik potong 104.5 mg/dL berdasarkan kurva ROC, kolesterol non HDL memiliki AUC 0.846, tingkat sensitifitas 80% dan spesifisitas 78,1% (p <0.001). Hasil analisis bivariat menunjukkan kolesterol non HDL yang tinggi berhubungan derajat stenosis koroner berat dengan rasio prevalens 3,385 (p<0.001). Analisis multivariat regresi logistik menunjukkan kolesterol non HDL yang tinggi terbukti sebagai prediktor independen stenosis arteri koroner berat pada penderita sindroma koroner kronis di RSUP Sanglah.Simpulan: Kolesterol non HDL yang tinggi terbukti berhubungan secara independen dengan stenosis arteri koroner berat pada subyek SKK di RSUP Sanglah.